Combination of Adsorption-Diffusion Model with Computational Fluid Dynamics for Simulation of a Tubular Membrane Made from SAPO-34 Thin Layer Supported by Stainless Steel for Separation of CO2 from CH4 - Sadat Banitaba, Fatemeh; Mansourpour, Zahra; Fatemi, Shohreh (Journal of Membrane and Separation Technology, 2016)
Modeling of CO2/CH4 separation using SAPO-34 tubular membrane was performed by computational fluid dynamics. The Maxwell-Stefan equations and Langmuir isotherms were used to describe the permeate flux through the membrane and the adsorption-diffusion, respectively. Three-dimensional Navier-Stokes momentum balances in feed and permeate side coupled with adsorption-diffusion equations from the membrane were simultaneously solved by ANSYS FLUENT software. The velocity and concentration profiles were determined in both feed and permeate sides. There was a good agreement between simulation and experimental results and root mean square deviation for CH4 and CO2 are 0.13 and 0.1 (mmol m-2 s-1), respectively. The concentration polarization effect was observed in the results. The effect of the process variables were investigated to find out the most influential parameters in permeation and purity. The impact of operating conditions on separation were studied and showed that for enhancement of separation efficiency of CO2 from CH4, feed pressure, feed flow rate and tube radius and number of membrane modules in series should be increased, whereas flow configuration has less significant effect.